Intravenous and subsequent long-term oral tranexamic acid in enhanced-recovery primary total knee arthroplasty without the application of a tourniquet: a randomized placebo-controlled trial - Wang, Hao-Yang (BMC Musculoskelet Disord, 2019)
BACKGROUND: To assess the efficacy and safety of intravenous and subsequent long-term oral tranexamic acid (TXA) following total knee arthroplasty (TKA) without a tourniquet. METHODS: In this double-blinded trial, 118 patients undergoing primary TKA were randomized into two groups: the patients in group A received intravenous TXA at 20-mg/kg 10 min before the surgery and 3 h postoperatively, and then oral 1 g TXA from postoperative day (POD) 1 to POD 14, and the patients in group B received intravenous TXA at 20-mg/kg 10 min before surgery and 3 h postoperatively, and then oral 1 g placebo from postoperative day (POD) 1 to POD 14. The primary outcome was total blood loss. Secondary outcomes included ecchymosis area and morbidity, postoperative transfusion, postoperative laboratory values, postoperative knee function and length of hospital stay. Complications, and patient satisfaction were also recorded. RESULTS: The mean total blood loss was lower in Group A than in Group B (671.7 ml vs 915.8 ml, P = 0.001). There was no significant difference in the transfusion rate between the two groups. Group A had a higher hemoglobin than Group B on POD 3 (106.0 g/L vs 99.7 g/L, P = 0.001). However, no significant difference was found for Hb or hematocrit on POD 1 or POD 14 between the two groups. Patients in Group A had less ecchymosis morbidity (7 vs 38, P = 0.001), smaller ecchymosis area (1.6 vs 3.0, P = 0.001) than Group B. The blood coagulation level as measured by fibrinolysis (D-Dimer) was lower in Group A than in Group B on POD 1 and POD 3 (4.6 mg/L vs. 8.4 mg/L, respectively, P = 0.001; 1.5 mg/L vs. 3.3 mg/L, respectively, P = 0.001). However, there was no significant difference on POD 14, and the fibrin degradation products showed the same trend. Patients in Group A had less swelling than those in Group B on POD 3 and POD 14. The circumference of the knee was 43.1 cm vs. 46.1 cm (POD 3, P = 0.001) and 41.4 cm vs. 44.9 cm (POD 14, P = 0.001) in Group A vs Group B, respectively. Nevertheless, the circumference of the knee in the two groups was similar on POD 1 and POD 3 M. No significant differences were identified in knee function, pain score, or hospital stay. No significant differences were identified in thromboembolic complications, infection, hematoma, wound healing and patients satisfaction between the two groups. CONCLUSION: Intravenous and subsequent long-term oral TXA produced less blood loss and less swelling and ecchymosis compared with short-term TXA without increasing the risk of complications. TRIAL REGISTRATION: The trial was registered in the Chinese Clinical Trial Registry (ChiCTR-IPR-17012264).